Hubungan Antara Preeklampsia Dengan Kejadian Bayi Berat Lahir Rendah (BBLR) Di Rumah Sakit Umum Daerah Sanjiwani Gianyar - I Made Adi Putra Wiguna; Ni Putu Diah Witari; Anak Agung Gede Raka Budayasa (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Low birth weight (LBW) is a condition when babies are born below normal weight limits 2.500 grams and is the highest cause of death in neonates. One of the risk factors for LBW is preeclampsia. Preeclampsia is a common condition in pregnant women which is characterized by blood pressure of 140/90 mmHg and proteinuria, which is 300 mg or more of protein in urine per 24 hours or 30 mg/dL (1+ on the dipstick) according to the results of the urine sample test. Preeclampsia in pregnant women can affect the condition of the fetus conceived by pregnant women from the period of pregnancy, childbirth, and postpartum. The purpose of this study was to determine the relationship between preeclampsia and LBW at the Sanjiwani Regional General Hospital, Gianyar. This study used an analytic observational method with a cross sectional study design. This study is considered to be unpaired categorical scale. Research data collection is done through secondary data in the form of medical records between 2018 - 2020. Bivariate data analysis is done to determine the relationship between variables using the chi-square test with a significance level of 0.05. The results showed that the p value = 0.000 and the PR was 7.917 (95% CI =2,569-24,395). As such, there is a significant relationship between preeclampsia and the incidence of LBW. Keywords: low birth weight baby, preeclampsia, sanjiwani regional hospital gianyar